Knowledge and Attitude of Health Care Workers (HCW) About Covid-19 Pandemic in the Department of Pathology - Mariam Khan Qamar , Armaghana Qamar Khan , Aamir Afzal , Shahid Ahmad Abbasi , Atif Abbas , Fauzia Khan (Journal of Islamic International Medical College, 2021)
Objective: To assess the Knowledge and Attitude of healthcare workers about COVID-19 in the Department of Pathology